Cancer nanotheranostics - Gopinath, P.; Uday Kumar, S.; Matai, Ishita; Bhushan, Bharat; Malwal, Deepika; Sachdev, Abhay; Dubey, Poornima (Springer Singapore, 2015)
This Brief provides a clear insight of the recent advances in the field of cancer theranostics with special emphasis upon nano scale carrier molecules (polymeric, protein and lipid based) and imaging agents (organic and inorganic).